2017
DOI: 10.20937/rica.2017.33.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Estimación De Emisiones De Mercurio en Las Plantas Carboeléctricas De México

Abstract: Palabras clave: carbón, contaminación atmosférica, contaminantes atmosféricos tóxicos, factores de emisión, generación de electricidad RESUMENReducir las emisiones de mercurio en la atmósfera es uno de los acuerdos tomados en la Convención Internacional de Minamata, llevada a cabo en Kumamoto Japón en 2013. Ante este compromiso se estableció como objetivo principal de este estudio la estimación de la variación temporal mensual de las emisiones de mercurio por unidad de generación para cada una de las tres carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Considering how toxic and persistent is the presence of mercury in the atmosphere, Sosa et al (2014Sosa et al ( , 2017 investigated the mercury emissions from 2012 to 2013 using monthly coal consumption data provided directly by the industrial sector for the three Mexican coal-fired power plants, and Fuentes et al (2017) reported the spatiotemporal variability of atmospheric mercury using per-day and per-generatingunit data of one coal-fired power plant (CETEPEC) in Mexico. Fuentes et al (2017) reported that mercury concentration in the coal from a Kansas mine in the USA, which is used by CETEPEC, was 0.335 mg Hg/kg of coal, and Múgica et al (2003) reported a concentration of 0.333 mg Hg/kg in Mexican coal.…”
Section: Mercury Emissions From Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Considering how toxic and persistent is the presence of mercury in the atmosphere, Sosa et al (2014Sosa et al ( , 2017 investigated the mercury emissions from 2012 to 2013 using monthly coal consumption data provided directly by the industrial sector for the three Mexican coal-fired power plants, and Fuentes et al (2017) reported the spatiotemporal variability of atmospheric mercury using per-day and per-generatingunit data of one coal-fired power plant (CETEPEC) in Mexico. Fuentes et al (2017) reported that mercury concentration in the coal from a Kansas mine in the USA, which is used by CETEPEC, was 0.335 mg Hg/kg of coal, and Múgica et al (2003) reported a concentration of 0.333 mg Hg/kg in Mexican coal.…”
Section: Mercury Emissions From Mexicomentioning
confidence: 99%
“…These estimates were calculated using the USEPA methodology, assuming a mercury concentration in coal of 0.113 mg/kg. Table IV shows mercury emissions estimated by Sosa et al (2017) using the mercury emission rate.…”
Section: Mercury Emissions From Mexicomentioning
confidence: 99%